Proceedings of the Graduate Research in Education Seminar (GREduc) 2017 - Faculty of Educational Studies (Faculty of Educational Studies, 2017)
The Graduate Research in Education (GREDuc) 2017 Seminar, held on December 16, 2017, and organized by the Faculty of Educational Studies, Universiti Putra Malaysia, focused on the theme Promoting Research Culture Excellence in Education and Human Resource Development